কাইয়ুম চৌধুরীর রেখাচিত্র - চৌধুরী,কাইয়ুম. 1934- (ঢাকা : ঐতিহ্য, 2007)
Album of drawings by a 20th century painter from Bangladesh.
Bengali and English.
Keywords: Chowdhury, Qayyum, -- 1934-; Chowdhury, Qayyum, -- 1934-